Adolescents’ self-perceived health, life satisfaction and subjective vitality during the COVID-19 pan-demic: an analysis based on education level, gender and physical activity status. - Carlos Mata; Marcos Onofre; Athanasios Papaioannou; João Martins (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
During the COVID-19 pandemic, disruptions to adolescents' routines manifested in increased sedentary behaviors, reduced physical activity (PA), diminished social contacts, and adverse effects on mental health. The study's objective was to analyze and compare adolescents' self-perceptions concerning health, vitality, and life satisfaction based on gender, PA, and education levels during the pandemic's restrictive timeframe before the January 2021 lockdown. A total of 1369 Portuguese students (621 boys and 748 girls; Mage: 14.4 years; SD: 1.74) participated in this study. Group differences were analyzed via ANCOVA, considering age, standardized BMI, socioeconomic status, and daily moderate-to-vigorous PA both pre- and during the pandemic. Only 3.1% of adolescents adhered to international PA guidelines. Results indicated generally low levels of adolescents' health self-perceptions, particularly among girls. The study sheds light on adolescents' self-perceptions of health and well-being during the COVID-19 pandemic, emphasizing the associations between restrictive measures and adolescents' health perceptions and PA levels. Future studies are necessary to assess students' self-perceptions upon returning to normalcy and understand lingering negative effects on adolescents' well-being.